The Fiscal and Human Costs of Life Without Parole - Leigey, Margaret E. (The prison journal, 2019)
In recent decades, the United States has increasingly relied on life-without-parole (LWOP) sentences. Due to its indeterminacy, such a sentence involves tremendous fiscal and human costs. This study first examines the use of LWOP in Louisiana, Pennsylvania, and Massachusetts, which have high percentages of LWOP inmates in their prison populations. After a comparison of what type of convictions trigger LWOP, we discuss the impact the LWOP population has had on the states’ correctional systems. We then assess the human costs of LWOP by problematizing the indeterminacy of the sentence and comparing how international and domestic courts have restricted its use.